Spectroscopic Study the Air-Processed Degradation Mechanism of Inverted Organic Solar Cells - Wang, Minshuai; Cai, Xiaomei; Huang, Yinghong; Zheng, Kai; Li, Fumin (Frontiers in Physics, 2020)
Organic solar cell is promising for the next generation photovoltaic technology owing to its low cost and flexibility. The possibility of large-area roll-to-roll production has attracted worldwide industrial interest. However, the instability and glove-box process still impede the industrial production of organic solar cells. In this paper, air-processed degradation mechanism has been investigated. The air-processed degradation mechanism of the organic solar cells is ascribed that the PEDOT:PSS interfacial layer is oxidized by oxygen and the active layer p-DTS(FBTTh2)2 tend to be affect by absorbed water. The air-processed degradation of PEDOT:PSS interfacial layer results from the oxidation and desulphurization of PEDOT:PSS, which caused huge efficiency loss. The active layer of p-DTS(FBTTh2)2:PC71BM tended to affect by absorbed water, which led to fatal results. The research on these unresolved degradation mechanisms enables us to choose the suitable materials and get stable performance in the air-processed situation.